TRANSTORNO DO ESPECTRO AUTISTA E AGROTÓXICO: ACOMPANHANDO UM PROBLEMA RECENTE NA OPINIÃO PÚBLICA - DUTRA, DAYANE (2023)
This research aims to promote a contemporary discussion on the correlation between pesticide exposure as a risk factor for the development of Autism Spectrum Disorder (ASD). Scientifically, this disorder is defined as a permanent neurological condition characterized by clinical manifestations observed through the impairment of three specific areas of neurodevelopment: deficits in social skills, deficits in communication skills (verbal and non-verbal), and the presence of restricted, repetitive and stereotyped behaviors, interests and/or activities, which become more visible when the individual is inserted into the social context. Due to its heterogeneity and complexity, in addition to the significant increase in the prevalence of cases worldwide, the disorder has been considered a major public health problem, with family, emotional, and also financial impacts. And while the apparent increase in prevalence may be due in part to changing diagnostic practices and increased awareness of this disorder, it does not fully explain it, as its etiology is still inconclusive. Scientific evidence points out that the causes for the development of the disease are linked to multifactorial inheritance (genetic and environmental factors). To map the study we took as our bibliographic base scientific productions in the various areas of knowledge, configuring it, methodologically, as an interdisciplinary literature review. After reading, compiling and analyzing the data, a variety of studies were found to support the hypothesis about the association between early exposure to pesticides, mainly related to Organochlorines and Organophosphates, as an environmental risk factor for the development of ASD. Moreover, there is a need to expand this discussion, especially in Brazil, seeking to give greater visibility to this issue, working not only an alert, but emerging from the importance of thinking and/or rethinking an urgent approach strategy to reduce the use of pesticides and encourage the adoption of less harmful practices, to ensure the reduction of risk to human health and environmental preservation.